Observations of discrete magnetosonic waves off the magnetic equator. Issue 22 (27th November 2015) - Zhima, Zeren; Chen, Lunjin; Fu, Huishan; Cao, Jinbin; Horne, Richard B.; Reeves, Geoff
Abstract: Fast mode magnetosonic waves are typically confined close to the magnetic equator and exhibit harmonic structures at multiples of the local, equatorial proton cyclotron frequency. We report observations of magnetosonic waves well off the equator at geomagnetic latitudes from −16.5°to −17.9° and L shell ~2.7–4.6. The observed waves exhibit discrete spectral structures with multiple frequency spacings. The predominant frequency spacings are ~6 and 9 Hz, neither of which is equal to the local proton cyclotron frequency. Backward ray tracing simulations show that the feature of multiple frequency spacings is caused by propagation from two spatially narrow equatorial source regions located at L  ≈ 4.2 and 3.7. The equatorial proton cyclotron frequencies at those two locations match the two observed frequency spacings. Our analysis provides the first observations of the harmonic nature of magnetosonic waves well away from the equatorial region and suggests that the propagation from multiple equatorial sources contributes to these off‐equatorial magnetosonic emissions with varying frequency spacings. Key Points: Magnetosonic waves at off‐equatorial region exhibits harmonic structure The multiple frequency spacings are the same as the equatorial proton cyclotron frequency Magnetosonic emissions at off‐equatorial region originate from multiple equatorial sources